Regulation of Underground Space in Realising Community Welfare and Legal Certainty for Investment - Erni Rohaini; Lina Jamilah (Journal La Sociale, 2024)
The purpose of this research is to analyze and discover the regulation of underground space in realizing public welfare and legal certainty for investment and offer future concepts of underground space regulation in realizing public welfare and legal certainty for investment. This research is normative juridical research with statutory, historical, comparative, and conceptual approaches. The findings of this research show: (a) it has not been regulated regarding property rights, utilization of underground space for private and public, the authority of the central and local governments as well as the authority of notaries and/or PPAT, institutions, and the implementation of underground space. (b) has been regulated but the norms are unclear and not yet comprehensive regarding rights to underground space in the form of Right of Use, HPL and HGB. (c) there are still norms that regulate optional in the regulation of underground space; (d) there are conflicts of legal norms between sector laws. This research concludes that the current underground space regulation is inadequate to support welfare and legal certainty for investment, because there is no support from the Underground Space Law as an instrument of renewal. In addition, the main concept of the Draft Basement Law for the future is directed at public welfare and legal certainty for investment. The draft builds on the philosophical foundation of the welfare state the sociological foundation of the need for underground space utilization, the recognition of rights to underground space, and the juridical foundation of legal certainty.